High-Flow Nasal Oxygen for Severe COVID-19 Pneumonia in Greek Patients: A Prospective Observational Study - CHAMILOS, GEORGIOS; KOFTERIDIS, DIAMANTIS P; ON BEHALF OF THE UNIVERSITY HOSPITAL OF HERAKLION COVID-19 STUDY GROUP; FILIPPATOS, THEODOSIOS D; AKOUMIANAKI, EVANGELIA; AKOUMIANAKIS, IOANNIS; IOANNOU, PETROS (Kurume medical journal, 2022)
Introduction: High-flow nasal oxygen (HFNO) and prone positioning may improve outcomes of coronavirus disease 2019 (COVID-19) patients treated in the intensive care unit (ICU). The aim of this study was to describe outcomes following the timely application of HFNO and prone positioning in COVID-19 patients treated in a ward setting. Methods: The study included 89 prospectively recruited subjects at the COVID-19 ward unit of the University Hospital of Heraklion, Greece, between March and December 2020. Results: Seventy-four (83%) of the 89 subjects in the study had severe COVID-19. Of those, 33 (45%) required HFNO treatment and prone positioning and 15 (45%) were transferred to the ICU, with 4 of them being intubated. Severe COVID-19 and HFNO needs were associated with an increased pneumonia severity index (PSI) score on admission and a worse PaO2/FiO2 ratio. In multivariate analysis, PSI was the only independent predictor of subsequent HFNO needs (OR=1.022). Overall intubation and mortality rates were 5.6% and 3.4%, respectively. Conclusion: This study shows that for patients with severe COVID-19 hospitalized in medical wards, standard COVID-19 treatment, along with the timely utilization of HFNO and prone positioning, resulted in excellent outcomes with fewer ICU admission rates.